2022
DOI: 10.1186/s43046-022-00105-8
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of postoperative radiation therapy following plastic surgical resection of recurrent ear keloid: a single institution experience

Abstract: Background Ear keloids are abnormal continuously growing healing process following cutaneous injury. Surgical excision is the standard treatment strategy; however, 50–80% of cases develop recurrence. Adjuvant radiotherapy (RT) is commonly offered with a marked decrease in the recurrence rate. The variation in RT protocols used in different studies leads to a bias of results analysis. The aim is to present our experience of using surgical excision with postoperative radiotherapy for recurrent ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Keloids in other locations were more irregular in shape, had high tension, and had a relatively low local control rate, which was similar to the results of previous studies. [19][20][21][22][23][24] As in the general population, hypertension was more common among older patients in this study. Although univariate analysis suggested that hypertension was a prognostic factor for the need for postoperative adjuvant electron RT for keloids, multivariable analysis revealed that it was not an independent factor.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Keloids in other locations were more irregular in shape, had high tension, and had a relatively low local control rate, which was similar to the results of previous studies. [19][20][21][22][23][24] As in the general population, hypertension was more common among older patients in this study. Although univariate analysis suggested that hypertension was a prognostic factor for the need for postoperative adjuvant electron RT for keloids, multivariable analysis revealed that it was not an independent factor.…”
Section: Discussionsupporting
confidence: 50%
“…Keloids in other locations were more irregular in shape, had high tension, and had a relatively low local control rate, which was similar to the results of previous studies. [19–24]…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies highlight age, burn size, and inhalation injury as predictors of mortality and extended LOS post-acute burn injury. 21 The average LOS in our study was found to be 8.85 ± 0.81 days, with the majority of patients experiencing prolonged stays, lasting more than 6 days. The length of stay is strongly correlated with the degree of burn injury.…”
Section: Discussionmentioning
confidence: 48%
“…Orthovoltage x-ray therapy is commonly used for both curative and palliative radiotherapy treatments of some super cial conditions and skin cancers [1][2][3][4][5][6]. Orthovoltage x-rays are characterized by the lack of skin-sparing and relative simplicity compared to megavoltage radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…It could be a cost effective alternative for the treatment of super cial cancer patients specially in busy radiotherapy departments. Orthovoltage could be used to treat squamous cell carcinomas, basal cell carcinomas, bony metastases, keloids, dermatological conditions, mycosis fungoids, in ammatory disorders, degenerative disorders, hypertrophic disorders, and functional disorders [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%